Experience of Women of Reproductive Age in Early Detection of Cervical Cancer Through IVA Examination - Gita Permata Mulya; Masrina Munawarah Tampubolon; Didi Kurniawan (CV. Rayyan Dwi Bharata, 2023)
Cervical cancer ranks second as a cancer that causes death in women worldwide. Thus, it is necessary to increase efforts to treat cervical cancer by carrying out early detection through VIA examination. This study aims to explore the experiences of women of childbearing age who have had IVA examinations. This research method uses qualitative research through a phenomenological approach. The participants in this study were 5 main participants and 1 supporting participant who were selected based on a purposive sampling technique. The data analysis used is the Colaizzi technique. The results of this study resulted in 4 themes, namely: (1) Initiatives for early detection, (2) Feelings of WUS during the IVA test process, (3) Support systems in undergoing IVA tests, (4) Expectations for IVA test services. Conclusion: Women of childbearing age who have had an IVA examination have a high self-initiative to take an IVA test. The participants thought that the IVA examination was very useful for early detection of cervical cancer. Feelings of embarrassment and fear were not obstacles for the participants to carry out the IVA examination. It is hoped that further IVA examinations can be carried out with wider counseling and given a room that supports more privacy.